INNOVATIONS IN THE ECONOMY OF THE AGRARIAN SECTOR - A.M. Balkibaeva; G.M. Mukasheva; M.S. Tolysbaeva; A.M. Aralova; Zh.Zh. Gabbassova (Academic Journal of Physical and Chemical Sciences, 2019)
In modern conditions, one of the main factors of agricultural development, which helps in ensuring the sustainable development of the agro-industrial complex, is innovation. Its effectiveness depends on the state of the external and internal economic environment, the availability of the necessary conditions for the introduction and rational use of innovative products. An innovative approach in relation to the agrarian sphere consists of: first, a study of the role and degree of influence of institutions that ensure the success of the transformation process in the agrarian sphere as a whole on the basis of modernization. Secondly, the creation of the necessary institutional environment and, finally, thirdly, the implementation in economic practice of the results of research and development in the form of new forms of organization and management, financing and crediting of production; new approaches to training, retraining and staff development; new technologies, new equipment, new fertilizers, etc.